1995
DOI: 10.1159/000310599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strabismus Surgery on Refraction in Children

Abstract: We assessed 115 eyes of 59 children with esotropia 2–3 months postoperatively to evaluate the effects of strabismus surgery on refraction. Three variables were measured: spherical equivalent, and cylinder power and axis. The mean changes in spherical equivalent were non-significant. The axis of postoperative astigmatism moved towards ‘with-the-rule’, thus improving refraction. The amount of recession and the consequent changes in cylinder power were inversely related. The results showed a significant change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 6 publications
(8 reference statements)
4
34
0
9
Order By: Relevance
“…Kwitko and colleagues 116 found that surgery on rabbit EOM's caused significant changes in corneal topography in some cases. There have also been several reports of highly significant changes in astigmatism [117][118][119][120][121] and corneal topography 122,123 following surgery for strabismus in human subjects.…”
Section: Astigmatism and Extraocular Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kwitko and colleagues 116 found that surgery on rabbit EOM's caused significant changes in corneal topography in some cases. There have also been several reports of highly significant changes in astigmatism [117][118][119][120][121] and corneal topography 122,123 following surgery for strabismus in human subjects.…”
Section: Astigmatism and Extraocular Musclesmentioning
confidence: 99%
“…Alteration in muscle tension (and subsequent alteration in the force applied by the muscles to the anterior globe) or changes in tractional forces due to surgery have both been suggested as possible causes of these topographical changes. 119,121 Factors relating to surgical recovery (for example, inflammation in and around the globe) may also influence the corneal topography following strabismus surgery. 123 It remains to be seen whether alterations in EOM tension from everyday tasks such as convergence and eye movement also cause significant changes in corneal topography and astigmatism.…”
Section: Astigmatism and Extraocular Musclesmentioning
confidence: 99%
“…A influência na refração de cirurgia nos músculos extraoculares não está bem compreendida, havendo poucos relatos e freqüentemente contraditórios (1)(2)(3)(4)(5)(6)(7)(8) . Entretanto, há estudos conclusivos acerca da influência da ressecção de pterígio e da cirurgia vítreo-retiniana na curvatura da córnea (15)(16)(17) .…”
Section: Discussionunclassified
“…Preslan et al (2) , estudando uma miscelânea de casos de estrabismo, encontraram um incremento muito discreto (0,15 dioptria) no astigmatismo a-favor-da-regra, mantendo-se inalterado o equivalente esfé-rico. No entanto, Denis et al (3) , incluindo em seu estudo mús-culos retos e oblíquos, mostraram que não há mudança no montante do astigmatismo ou do equivalente esférico, mas sim no eixo, havendo uma tendência em se obter maior número de astigmatismos a-favor-da-regra. Fix e Baker (4) , por outro lado, obtiveram mudanças clinicamente significativas em 2% dos casos pediátricos e em 25% dos adultos.…”
Section: Introductionunclassified
“…Mudança no eixo do astigmatismo a favor da regra foi constatado por Denis e col., ocorrendo principalmente nas cirurgias de retrocesso do músculo oblíquo inferior. A combinação de técnicas cirúrgicas de retrocesso de músculo reto medial e de músculo oblíquo inferior associada ao "tucking" do músculo reto lateral também modificam o eixo do astigmatismo a favor da regra (15) . A indicação para a prescrição de correção óptica do astigmatismo está relacionada a dificuldade visual ou astenopia (com ou sem cefaléia) referidos pelo paciente.…”
Section: Atualização Continuadaunclassified